2021
DOI: 10.1113/jp282228
|View full text |Cite
|
Sign up to set email alerts
|

Conventional rigid 2D substrates cause complex contractile signals in monolayers of human induced pluripotent stem cell‐derived cardiomyocytes

Abstract: Human induced pluripotent stem cell‐derived cardiomyocytes (hiPSC‐CM) in monolayers interact mechanically via cell–cell and cell–substrate adhesion. Spatiotemporal features of contraction were analysed in hiPSC‐CM monolayers (1) attached to glass or plastic (Young's modulus (E) >1 GPa), (2) detached (substrate‐free) and (3) attached to a flexible collagen hydrogel (E = 22 kPa). The effects of isoprenaline on contraction were compared between rigid and flexible substrates. To clarify the underlying mechanisms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
(143 reference statements)
1
8
0
Order By: Relevance
“…The β-adrenergic agonists dobutamine and isoprenaline caused distinct electrophysiological effects that were paralleled in the two experimental groups. There was an increase in the spontaneous rate (decreased cycle length) in both cell systems, indicating an increased activity of the funny channel ( I f ) by cAMP, as reported in nodal cardiac tissue and previously reported in iPSC-CM systems [ 24 ]. The significant and comparable expression of HCN4 in both FM and MM groups indicates that the degree of electrophysiological differentiation was similar in both groups.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The β-adrenergic agonists dobutamine and isoprenaline caused distinct electrophysiological effects that were paralleled in the two experimental groups. There was an increase in the spontaneous rate (decreased cycle length) in both cell systems, indicating an increased activity of the funny channel ( I f ) by cAMP, as reported in nodal cardiac tissue and previously reported in iPSC-CM systems [ 24 ]. The significant and comparable expression of HCN4 in both FM and MM groups indicates that the degree of electrophysiological differentiation was similar in both groups.…”
Section: Discussionsupporting
confidence: 77%
“…In both experimental groups, decreased contraction duration suggests that the lustotropic actions of adrenergic stimulation were equally present, but in neither group was there a significant positive inotropic response ( Figure 6 ). This form of adrenergic contractile response has been previously reported in hiPSC-CMs (e.g., [ 24 ]) and is thought to be based on the poorly developed sarcoplasmic reticulum systems within these cells, a feature that is unaltered by culturing on the specialized matrix system (MatrixPlus Cellvo™).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…A contractility platform and software (CellOPTIQ, Clyde Biosciences), based on video pixel displacement, was used to measure 2D hiPSC-CM contractility ( Sala et al, 2018 ; Saleem et al, 2020b ; Huethorst et al, 2022 ). 2D hiPSC-CMs were imaged directly in plates by an inverted fluorescence microscope (Zeiss) using a ×40 objective.…”
Section: Methodsmentioning
confidence: 99%
“…HiPSC-CMs are a useful in vitro model to assess the molecular and functional effects of CCM on human cardiac tissue ( Feaster et al, 2021 ). However, contractile studies in hiPSC-CMs have been limited as a result of immature contractile properties when plated as conventional 2D monolayers on stiff substrates (i.e., glass or plastic) ( Feaster et al, 2021 ; Korner et al, 2021 ; Huethorst et al, 2022 ; Narkar et al, 2022 ). We previously demonstrated that 2D monolayer hiPSC-CMs, on flexible substrate, displayed increased contraction and calcium handling properties when acutely stimulated with standard CCM pulse.…”
Section: Introductionmentioning
confidence: 99%